The global debate on the future of artificial intelligence: The need for international regulation and opportunities for German foreign policy - Marcel Dickow; Daniel Voelsen (Stiftung Wissenschaft und Politik (SWP), 2018)
With the current developments in the field of artificial intelligence, the process of digitalisation has reached a new stage. Artificial intelligence makes it possible to analyse the large amounts of data collected today in completely new ways. Companies and countries are spending considerable resources to take advantage of these analytical possibilities. However, artificial intelligence is also dependent on the quality of the underlying data; it is completely unsuited for many tasks and has, so far, largely escaped human control. Germany should therefore use its influence in international forums to regulate the use of artificial intelligence in politically sensitive areas. In addition, the Federal Government should carefully examine on what data basis, for what purposes, and under what conditions artificial intelligence can make a contribution to the planning of foreign policy strategy.
Keywords: 320